Synthesis and Exploration of Abscisic Acid Receptor Agonists Against Dought Stress by Adding Constraint to a Tetrahydroquinoline‐Based Lead Structure. Issue 23 (18th June 2021) - Bojack, Guido; Baltz, Rachel; Dittgen, Jan; Fischer, Christian; Freigang, Jörg; Getachew, Rahel; Grill, Erwin; Helmke, Hendrik; Hohmann, Sabine; Lange, Gudrun; Lehr, Stefan; Porée, Fabien; et al.
Abstract: New oxotetrahydroquinolinyl‐ and oxindolinyl sulfonamides interacting with RCAR/(PYR/PYL) receptor proteins were identified as lead structures against drought stress in crops starting from protein docking studies of a sulfonamide lead structure, followed by in‐depth SAR studies. Optimized five to six step synthetic approaches via substituted amino oxo‐tetrahydro‐quinolines and amino oxo‐indolines as essential intermediates gave access to the envisaged oxo‐tetrahydroquinolinyl and oxindolinyl sulfonamides. Whilst oxo‐tetrahydroquinolinyl sulfonamides with additional carbon substituents or spiro‐cycloalkyl groups exhibited only low to moderate target affinities, the corresponding spiro‐oxindolinyl and oxo‐tetrahydroquinolinyl sulfonamides carrying optimized N ‐substituents revealed strong interactions with RCAR/(PYR/PYL) receptor proteins in Arabidopsis thaliana . Remarkably, the in vitro activity observed for these new compounds was on the same level as observed for the naturally occurring plant hormone in line with strong efficacy against drought stress in‐vivo (canola and wheat as broad‐acre crops). Abstract : In the SAR‐study described herein, the analysis, exploration, and optimization of a lead structure that had shown good initial in vitro activity by interacting with RCAR/(PYR/PYL) receptor proteins, a key biochemical target of plant hormone abscisic acid. In the course of the in‐depth SAR study, several new potent sulfonamide lead structures with higher target affinity and, more importantly, improved in vivo efficacy against drought stress in broad‐acre crops canola and wheat compared with the initial lead structure were identified.